2021
DOI: 10.2478/jtim-2021-0025
|View full text |Cite
|
Sign up to set email alerts
|

Effects of des-acyl ghrelin on insulin sensitivity and macrophage polarization in adipose tissue

Abstract: Background and Objectives Obesity is the accumulation of adipose tissue caused by excess energy in the body, accompanied by long-term chronic low-grade inflammation of adipose tissue. More than 50% of interstitial cells in adipose tissue are macrophages, which produce cytokines closely related to insulin resistance. Macrophage biology is driven by two polarization phenotypes, M1 (proinflammatory) and M2 (anti-inflammatory). This study aimed to investigate the effect of gastric hormone des-acy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 49 publications
1
21
0
Order By: Relevance
“…Previous observations have shown that obese mice and humans have lower DAG levels than their normal-weight counterparts where AG levels are similar, suggesting that obesity may reflect a relative DAG deficiency 8 , 35 , 36 Our study found that compared with VFA normal group, VFA obese individuals with high or normal BMI have lower DAG levels and higher HOMA-IR. VFA was significantly negatively correlated with DAG levels.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Previous observations have shown that obese mice and humans have lower DAG levels than their normal-weight counterparts where AG levels are similar, suggesting that obesity may reflect a relative DAG deficiency 8 , 35 , 36 Our study found that compared with VFA normal group, VFA obese individuals with high or normal BMI have lower DAG levels and higher HOMA-IR. VFA was significantly negatively correlated with DAG levels.…”
Section: Discussionsupporting
confidence: 55%
“… 37 Besides, DAG can inhibit inflammation of adipose tissue caused by HFD and decrease macrophage infiltration of adipose tissue, thus alleviating obesity and improving insulin sensitivity in rodents. 36 In contrast, administering AG reduces energy expenditure, enhances gene expression of fat storage-promoting enzymes in adipose tissue, and consequently promotes adipose tissue deposition in animal models. 38 No correlation between AG concentrations and body fat mass was found in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in humans have shown that there are two subtypes of human liver macrophages, which segregate into proinflammatory and immunoregulatory phenotypes( 23 ). In our study, m rc1b ( 95 ), hmoxla ( 96 ), marco and cd63 ( 97 ) were placed in non-inflammatory macrophages in zebrafish liver, and these genes are known marker genes for immunoregulatory macrophages. It has been suggested that zebrafish liver non-inflammatory macrophages are similar to the profiles of CD68 + MARCO + cells in the human liver and that of resident Kupffer cells (KCs) in the rodent liver.…”
Section: Discussionmentioning
confidence: 99%
“…Among the current treatments of DR, the first and foremost is controlling blood sugar. Multiple evidence has pointed out that changing lifestyle, ameliorating insulin resistance, and repairing damaged β islet cell function can effectively delay the occurrence of DR [57][58][59]. DR is now recognized as a neuro-and vaso-degenerative rather than a microvascular disease, even in early stage when neuron loss is not evident [60,61].…”
Section: Discussionmentioning
confidence: 99%